Pelatihan Peregangan dan Relaksasi Otot Wajah pada Populasi Pekerja Kantor Pengguna Masker Sehari-hari di Jakarta, Indonesia - I Gusti Ayu Ratih Utari Mayun; Carolina Marpaung; Niko Falatehan; Yayuk Yuliarsi (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2022)
The COVID-19 pandemic requires office workers to wear masks in their daily lives. The reported side effects of wearing mask in long time period include orofacial pain. Self physiotherapy can be an easy solution in preventing and treating the pain. The purpose of this training is to train people to be able to strengthen and relax their facial muscles to prevent masticatory muscle pain. The online training was conducted on July 5, 2022 to 29 participants with Indonesian Attorney General's Office health workers as the majority. The evaluation results showed improvements in all training topics regarding personal protection, side effects of wearing masks, and ways to overcome side effects of wearing masks. Self physiotherapy skills could not be done in detail because of the limitations of online communication. Online training can improve participants' ability to practice stretching and muscle relaxation better.